2020
DOI: 10.1055/a-1124-3187
|View full text |Cite
|
Sign up to set email alerts
|

Transoral incisionless fundoplication with an ultrasonic surgical endostapler for the treatment of gastroesophageal reflux disease: 12-month outcomes

Abstract: Background Transoral incisionless fundoplication (TIF) with the Medigus ultrasonic surgical endostapler (MUSE) is a new intervention for the treatment of the gastroesophageal reflux disease (GERD). The aim of this study was to assess the 12-month clinical, functional, and endoscopic effects of TIF by MUSE. Methods Patients undergoing MUSE completed the GERD-Health Related Quality of Life (GERD-HRQL) and Reflux Symptom Index (RSI) questionnaires, and underwent endoscopy, esophageal 24-hour pH-impeda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 11 publications
1
26
0
1
Order By: Relevance
“…TIF 1.0 has been discontinued because TIF 2.0 achieves much better results[ 36 ]. The improved procedure has been evaluated in nine noncomparative studies[ 38 - 46 ] and in five RCTs[ 47 - 51 ] comprising 886 patients with moderate GERD without a large HH, Los Angeles grade C or D esophagitis, or Barrett´s esophagus (Table 3 ). Clinical success rates ranged from a modest 50% at 12 mo to as high as 92% at 10 years.…”
Section: Current Endoscopic Therapiesmentioning
confidence: 99%
“…TIF 1.0 has been discontinued because TIF 2.0 achieves much better results[ 36 ]. The improved procedure has been evaluated in nine noncomparative studies[ 38 - 46 ] and in five RCTs[ 47 - 51 ] comprising 886 patients with moderate GERD without a large HH, Los Angeles grade C or D esophagitis, or Barrett´s esophagus (Table 3 ). Clinical success rates ranged from a modest 50% at 12 mo to as high as 92% at 10 years.…”
Section: Current Endoscopic Therapiesmentioning
confidence: 99%
“…One study followed up 37 patients with GERD for 1 year after TIF 116 . The results showed that the scores for QoL, heartburn and regurgitation, and the reflux symptom index decreased; 65% of patients discontinued PPI completely and 25% reduced their dose of PPI by 50%.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, whether a combination of two kinds of invasive therapies can result in a double-overlapping effect and compensate for individual shortcomings remains unclear. A recent trial investigated the effect of a combination of MUSE TM and TIF, and satisfactory results showed that TIF with MUSE TM obviously improved the GERD-related symptoms; >90% of patients reduced or discontinued PPIs use [ 67 ].…”
Section: Introductionmentioning
confidence: 99%